Nested miRNA Secondary Structure Is a Unique Determinant of miR159 Efficacy in Arabidopsis - Imran, Muhammad; Liu, Tengfei; Wang, Zheng; Wang, Min; Liu, Shulin; Gao, Xinyan; Wang, Anning; Liu, Songfeng; Tian, Zhixi; Zhang, Min (Frontiers in Plant Science, 2022)
MicroRNAs (miRNAs) are 20- to 24-nucleotide small RNAs, and whenever a pri-miRNA precursor includes another miRNA precursor, and both of these precursors may generate independent non overlapping mature miRNAs, we called them nested miRNAs. However, the functional and regulatory roles of nested miRNA structures in plants are still unknown. In this study, the Arabidopsis nested miR159a structure, which consists of two nested miRNAs, miR159a.1, and miR159a.2, was used as a model to determine miRNA-mediated gene silencing in plants. Complementation analysis of nested miR159a structures revealed that the miR159a structure can differentially complement the mir159ab phenotype, and a duplex nested structure in the tail end region of the pre-miR159a fold back may have a possible dominant function, indicating the importance of the flanking sequence of the stem in the cleavage of the mature miRNA. Furthermore, continuously higher expression of the miR159a.2 duplex in the severe leaf curl phenotype indicates that miR159a.2 is functional in Arabidopsis and suggests that in plants, a miRNA precursor may encode multiple regulatory small RNAs. Taken together, our study demonstrates that the nested miR159a structure regulated by duplex mutations of miR159a has a unique pattern and provides novel insight into silencing efficacy of Arabidopsis miR159a.